Feasibility of using vapor compression refrigeration system for cooling steam plant condenser. (5th August 2016) - Hegazy, Ahmed; Rothan, Yahya; Engeda, Abraham
Highlights: A refrigeration system is proposed to cool the condenser of a steam power plant. Thermal efficiency improvement of 1.2–12% is achieved. The specific refrigerant mass does not depend on the ambient temperature. The specific refrigerant mass runs linearly with steam condenser temperature. Abstract: This study presents a proposal of a combined scheme for applying a vapor compression refrigeration system to cool the condenser of a steam plant. In this scheme the refrigerant (mostly liquid) leaving the throttle valve of the refrigeration system is circulated through the pipes of the shell and tube condenser, while the steam exhausting the plant turbine flows in the shell around the outer surfaces of the tubes. Thus, the refrigerant is vaporized and the steam is condensed. As a result, the maximum coefficient of heat transfer between the steam and refrigerant is achieved, and the condenser becomes compact. In addition, this combined scheme allows controlling the condenser temperature irrespective of the ambient conditions. Thermodynamic analysis of the steam plant, vapor compression refrigeration system and the proposed combined scheme has been developed. The results obtained using this analysis showed that an improvement in thermal efficiency of the combined scheme varying between 1.2 and 12% is achieved over that of the steam plant when the condenser is cooled, using ambient air, for the range of the ambient temperature of 30–50 °C and condenser temperature of 15–50 °C. The high value of the improvement is valid for higher ambient temperature and lower condenser temperature. Also, the results indicated that the specific refrigerant mass (mass of the refrigerant needed for condensing 1 kg of the steam) varies between 1.42 and 1.62 kg/kg at condenser temperature of 15 and 50 °C, respectively. This specific mass does not depend on the ambient temperature and runs linearly with steam condenser temperature.